2004
DOI: 10.1111/j.1478-4408.2004.tb00236.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various bioscouring systems on the accessibility of dyes into cotton

Abstract: The effect of four different enzymatic bioscouring systems for cotton have been compared in regard to the dyeability of reactive, cationic and acid dyes. The residual pectin content was determined and the results assessed in terms of dyeability against control samples prepared in the absence of enzyme. The capacity of a bifunctional reactive dye to cover the differences between fabrics treated with different bioscouring treatments was very good. Exhaustion of the cationic dye relative to alkaline scouring was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 1 publication
0
20
0
2
Order By: Relevance
“…The degree of whiteness attained in this procedure is lower than the degree of whiteness of the fibres bleached in a classic procedure with hydrogen peroxide. Dyeing with direct and reactive dyes was efficient and equal on fabrics that were differently scoured (Canal et al, 2004;Preša & Tavčer, 2009). Etters (Etters et al, 2001) did not notice any statistically significant difference between the rate of uptake, equilibrium exhaustion, or colour depth on the cotton substrate between the two fabrics that were either alkaline scoured or bioscoured.…”
Section: Influence Of Bioscouring On Further Finishing Proceduresmentioning
confidence: 99%
“…The degree of whiteness attained in this procedure is lower than the degree of whiteness of the fibres bleached in a classic procedure with hydrogen peroxide. Dyeing with direct and reactive dyes was efficient and equal on fabrics that were differently scoured (Canal et al, 2004;Preša & Tavčer, 2009). Etters (Etters et al, 2001) did not notice any statistically significant difference between the rate of uptake, equilibrium exhaustion, or colour depth on the cotton substrate between the two fabrics that were either alkaline scoured or bioscoured.…”
Section: Influence Of Bioscouring On Further Finishing Proceduresmentioning
confidence: 99%
“…In this point of view, chitosan is an excellent candidate for an eco-friendly textile chemical 10 . Chitosan (Polysaccharide) is a polycationic biopolymer having unique properties such as biodegradability, non-toxicity, antimicrobial activity and poly-cationic nature can be suitable molecule for a number of textile applications [11][12][13] .Chitosan is the deacetylated derivative of chitin that is the second most abundant polysaccharide found on earth next to cellulose 12,13 . The applications of chitosan has become the focus of research in multiareas such as pharmaceutical and medical applications, paper production, antimicrobial textiles finishes, fiber formation, wastewater treatment, biotechnology, cosmetics, food processing and agriculture due to its versatile chemical and physical properties 8,10,12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…The applications of chitosan has become the focus of research in multiareas such as pharmaceutical and medical applications, paper production, antimicrobial textiles finishes, fiber formation, wastewater treatment, biotechnology, cosmetics, food processing and agriculture due to its versatile chemical and physical properties 8,10,12,13 . The application of chitosan in cotton dyeing could reduce the use of dyes and dyes in wastewaters due to the increased dye exhaustion 11,14,15 . Moreover, the use of chitosan treatments in the textile dyeing process can represent a very sound practice due to its environment friendly characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…When dyed with bireactive dyes the dyeing showed excellent evenness and their capacity to cover differences in whiteness arising from different pretreatment processes was significant. On the contrary, the dyeings with acid and cationic dyes revealed, with large differences in dye exhaustions, that each enzymatic system produces different ionisable residues on the primary wall of the cotton fibre (Canal et al, 2004). The importance of charges and functional availability on the fibre surface after different bioscouring treatments for their dyeing behaviour was also exposed by Calafell and co-workers (Calafell et al, 2005).…”
mentioning
confidence: 96%
“…The dyeing behaviour of cotton fabrics treated with different enzymes by using reactive, cationic and acid dyes showed that cationic and acid dyes were more sensitive to the enzymatic treatment used as reactive dyes (Canal et al, 2004). When dyed with bireactive dyes the dyeing showed excellent evenness and their capacity to cover differences in whiteness arising from different pretreatment processes was significant.…”
mentioning
confidence: 99%